The 12/15-lipoxygenase pathway counteracts fibroblast activation and experimental fibrosis - Krönke, Gerhard; Reich, Nicole; Scholtysek, Carina; Akhmetshina, Alfiya; Uderhardt, Stefan; Zerr, Pawel; Palumbo, Katrin; Lang, Veronika; Dees, Clara; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2012)
Background: Idiopathic and inflammation-dependent fibrotic diseases such systemic sclerosis (SSc) impose a major burden on modern societies. Understanding endogenous mechanisms, which counteract fibrosis, may yield new therapeutic approaches. Lipoxins are highly potent lipid mediators, which have recently been found to be decreased in SSc. Objectives: To determine the potential role of 12/15-lipoxygenase (12/15-LO), the key enzyme for the synthesis of lipoxins, in fibrosis. Methods: Two mouse models for experimental dermal fibrosis (bleomycin-induced dermal fibrosis and tight-skin 1 mouse model) together with bone marrow transfers were used in wildtype and 12/15-LO -/- mice to elucidate the role of this enzyme during dermal fibrosis. Primary dermal fibroblasts of wildtype and 12/15-LO -/- mice, and 12/15-LO-derived eicosanoids, were used to identify underlying molecular mechanisms Results: In both models, 12/15-LO -/- mice exhibited a significant exacerbation of the fibrotic tissue response. Bone marrow transfer experiments disclosed a predominant role of mesenchymal cell-derived 12/15-LO in these antifibrotic effects. Indeed, 12/15-LO -/- fibroblasts showed an enhanced activation of the mitogen-activated protein-kinase pathway and an increased col 1a2 mRNA expression in response to stimulation with transforming growth factor β (TGFβ), whereas 12/15-LO-derived eicosanoids blocked these TGFβ-induced effects. Conclusions: These data indicate that 12/15-LO and its metabolites have a prominent antifibrotic role during dermal fibrosis. This opens new opportunities for therapeutic approaches in the treatment of fibrotic diseases.
CRIS-Team Scopus Importer:2020-11-20